Three‐Dimensional Coral‐Like Structure Constructed of Carbon‐Coated Interconnected Monocrystalline SnO2 Nanoparticles with Improved Lithium‐Storage Properties. Issue 7 (3rd May 2016) - Xu, Wangwang; Cui, Xiaodan; Xie, Zhiqiang; Dietrich, Grant; Wang, Ying
Abstract: The applications of alloying/dealloying materials as anode for LIB electrode are hindered by its dramatic volume variations and sluggish kinetics. Herein, to overcome these challenges, we report a facile and scalable approach fabricating coral‐like SnO2 /C composite electrodes through a top‐down strategy followed by a sol–gel carbon‐coating method. During the synthesis, well‐defined SnS2 nanoflowers and dopamine serve as structural template and carbon source for integrating the desired structure. The three‐dimensional coral‐like SnO2 /C composite exhibits a high reversible capacity of 648 mAh g −1 after 50 electrochemical cycles and a low capacity fading of 0.778 % per cycle from the 2nd to the 50th cycle, demonstrating an outstanding cycling stability. It also shows a discharge capacity of 1294, 784, 658, 532, and 434 mAh g −1 at a specific current of 100, 200, 500, 1000 and 2000 mAh g −1, respectively, and retains a specific capacity of 719 mAh g −1 when the specific current goes back to 100 mA g −1, displaying an excellent rate capability. Compared to SnS2 nanoflowers and bare interconnected SnO2 nanoparticles anode, the optimized coral‐like SnO2 /C composite shows significantly improved electrochemical performances in terms of rate capability and cycling reversibility, demonstrating great potential as superior anodes in next‐generation lithium ion batteries. Abstract : Shape matters : Coral‐like SnO2 /C composite electrodes, fabricated through a top‐down strategy followed by a sol–gel method of carbon coating, are compared to electrodes of SnS2 nanoflowers and interconnected SnO2 nanoparticles. The optimized coral‐like SnO2 /C composite shows significant improvements in electrochemical performance, especially in terms of the rate capability and cycling reversibility.